Dari Bencana Menuju Kesadaran: Refleksi Spiritual-Ekologis Banjir Bandang Aceh 2025 dan Relevansinya bagi Penguatan Komunitas Urban Melayu - Ainal Mardhiah; Cut Intan Hayati; Dewiyana; Qurratu Aini (Bansigom Na Publisher, 2026)
The 2025 Aceh flash flood and landslide disaster demonstrates that hydrometeorological hazards cannot be understood only as physical events, because their impacts are shaped by ecological degradation, social vulnerability, collective memory, and the meanings communities attach to loss and recovery. This article aims to formulate a spiritual-ecological reflection on the Aceh 2025 disaster and examine its relevance for strengthening urban Malay communities. The study uses an integrative literature review of twenty DOI-indexed scientific sources published between 2014 and 2026, covering disaster resilience, social capital, Islamic environmental ethics, flood management, local knowledge, and urban community adaptation. Thematic analysis identifies four interconnected findings: spirituality can strengthen meaning-making and active coping when it avoids fatalism; ecological awareness must be translated into watershed protection and nature-based solutions; social capital and place attachment are critical for preparedness and recovery; and mosques, neighbourhood networks, schools, and digital platforms can become resilience infrastructures. The article proposes a community-strengthening framework integrating spiritual literacy, ecological responsibility, social solidarity, and risk-sensitive urban governance for Malay urban contexts.